Information theoretic methods for studying population codes - Ince, Robin A. A. (2010)
Population coding is the quantitative study of which algorithms or representations are used by thebrain to combine together and evaluate the messages carried by different neurons. Here, we review ani nformation-theoretic approach to population coding. We first discuss how to compute the information carried by simultaneously recorded neural populations, and in particular how to reduce the limitedsampling bias which affects the calculation of information from a limited amount of experimental data.We then discuss how to quantify the contribution of individual members of the population, or theinteraction between them, to the overall information encoded by the considered group of neurons. Wefocus in particular on evaluating what is the contribution of interactions up to any given order to thetotal information. We illustrate this formalism with applications to simulated data with realistic neuronal statistic and  to real simultaneous recordings of multiple spike trains.